Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.